In situ processing of cellulose nanocomposites. (April 2016) - Ray, Dipa; Sain, Sunanda
Abstract: Nanocellulose has gained attention in recent times due to their light weight, high strength, stiffness, biodegradability and renewability. Natural fibres have been used as reinforcement in composites for past many years, but the use of nanocellulose as reinforcement in composites is relatively new. The main challenges of preparing nanocellulose based composites include (i) generation of nanocellulose from natural resources, (ii) production in larger scale, (iii) enhancing compatibility with hydrophobic polymers, and (iv) achieving uniform dispersion in polymer matrices. These challenges have encouraged researchers to innovate efficient processes and techniques to utilise the maximum benefit of such green nanoscopic materials. In situ fabrication of cellulose nanocomposites is one such technique of achieving uniform nanocellulose dispersion in polymer matrices and obtaining a stronger filler/matrix interface. This review summarises the recent progress in the field of in situ processing of cellulose nanocomposites.